Comparable efficacy and safety of brodalumab in obese and nonobese patients with psoriasis: analysis of two randomized controlled trials. (1st April 2020) - Hsu, S.; Green, L.J.; Lebwohl, M.G.; Wu, J.J.; Blauvelt, A.; Jacobson, A.A.
Summary: Background: Obesity is associated with psoriasis and negatively affects response to therapy. Objectives: To evaluate the efficacy and safety of brodalumab in nonobese vs. obese patients with psoriasis. Methods: This is a post hoc analysis of the prospective, phase III, multicentre, randomized, placebo‐ and active‐comparator‐controlled AMAGINE‐2 and AMAGINE‐3 trials, in which patients were randomized to treatment with brodalumab 210 mg every 2 weeks, ustekinumab or placebo for a 12‐week induction phase. At week 12, patients who received brodalumab 210 mg every 2 weeks continued brodalumab, those treated with ustekinumab continued ustekinumab, and those who received placebo switched to brodalumab 210 mg every 2 weeks. Patients were categorized by body mass index (BMI) category (< 30 or ≥ 30 kg m −2 ) and efficacy was evaluated using the physician‐rated Psoriasis Area and Severity Index and static Physician's Global Assessment instruments. Results: In total, 281 of 687 patients (40·9%) were obese. Skin clearance was comparable across BMI subgroups in brodalumab‐treated patients. Psoriasis Area and Severity Index 100% improvement rates in nonobese and obese patients at week 12 were 54·1% and 49·5%, respectively, and at week 52 they were 72·6% and 64·8%, respectively. Week 12 ustekinumab responses were lower than brodalumab responses and were 6–17% lower in obese than in nonobese patients. No appreciable differences in overall safety were observed between nonobese and obese patients. Conclusions: The efficacy and safety of brodalumab did not differ between patients with moderate‐to‐severe psoriasis who had a BMI < 30 kg m −2 or a BMI ≥ 30 kg m −2 .